The State of Migratory Landbirds in the East Asian Flyway: Distributions, Threats, and Conservation Needs - Yong, Ding Li; Heim, Wieland; Chowdhury, Sayam U.; Choi, Chang-Yong; Ktitorov, Pavel; Kulikova, Olga; Kondratyev, Alexander; Round, Philip D.; Allen, Desmond; Trainor, Colin R.; Gibson, Luke; Szabo, Judit K. (Frontiers in Ecology and Evolution, 2021)
With nearly 400 migratory landbird species, the East Asian Flyway is the most diverse of the world’s flyways. This diversity is a consequence of the varied ecological niches provided by biomes ranging from broadleaved forests to arctic tundra and accentuated by complex biogeographic processes. The distribution and migration ecology of East Asian landbirds is still poorly known, but a recent explosion in the number of studies tracking the migration of raptors, cuckoos, kingfishers and passerines has greatly increased our knowledge about the stopover and wintering ecology, and the migratory routes that link northeast Eurasia and the Asian tropics. The East Asian Flyway also supports the highest number of threatened species among flyways. Strong declines have been detected in buntings (Emberizidae) and other long-distance migrants. While the conservation of migratory landbirds in this region has largely focused on unsustainable hunting, there are other threats, such as habitat loss and increased pesticide use driven directly by land cover change and climate-related processes. Important knowledge gaps to be addressed include (1) threats affecting species in different parts of their annual cycle, (2) range-wide population trends, (3) ecological requirements and habitat use during the non-breeding season, and (4) conservation status of critical wintering sites (including understudied cultivated landscapes, such as rice fields) and migration bottlenecks along the flyway.